Solidarność . biuletyn informacyjny, no. 19, 1981 - [ed. Mirosław Przylipiak et al.], Niezależny Samorządny Związek Zawodowy "Solidarność" Zarząd Regionu Chełmskiego (NSZZ "Solidarność" woj. chełmskiego, 1981)
Creation and circulation: For trade-union use; After the introduction of the Martial Law publication suspended. Republished in 1989